Where are all the Mycobacterium avium subspecies paratuberculosis in patients with Crohn's disease? - Ellen S Pierce (Public Library of Science (PLoS), 2009)
Mycobacterium avium subspecies paratuberculosis (MAP) causes a chronic granulomatous inflammation of the intestines, Johne's disease, in dairy cows and every other species of mammal in which it has been identified. MAP has been identified in the mucosal layer and deeper bowel wall in patients with Crohn's disease by methods other than light microscopy, and by direct visualization in small numbers by light microscopy. MAP has not been accepted as the cause of Crohn's disease in part because it has not been seen under the microscope in large numbers in the intestines of patients with Crohn's disease. An analysis of the literature on the pathology of Crohn's disease and on possible MAP infection in Crohn's patients suggests that MAP might directly infect endothelial cells and adipocytes and cause them to proliferate, causing focal obstruction within already existing vessels (including granuloma formation), the development of new vessels (neoangiogenesis and lymphangiogenesis), and the "creeping fat" of the mesentery that is unique in human pathology to Crohn's disease but also occurs in bovine Johne's disease. Large numbers of MAP might therefore be found in the mesentery attached to segments of intestine affected by Crohn's disease rather than in the bowel wall, the blood and lymphatic vessels running through the mesentery, or the mesenteric fat itself. The walls of fistulas might result from the neoangiogenesis or lymphangiogenesis that occurs in the bowel wall in Crohn's disease and therefore are also possible sites of large numbers of MAP. The direct visualization of large numbers of MAP organisms in the tissues of patients with Crohn's disease will help establish that MAP causes Crohn's disease.